Framework for 2D SVG animation jitter - San, Lin Htet (2014)
It has been nearly half a century since the computer animation was invented and widely used all over the world but there is still great interest in imitating some effects of the traditional animation in modern computer animation. One such effect is the Jitter Effect of the traditional 2D animation that is apparent when a sequence of frames is drawn manually by hands. In this project, an application, called SVG Jitter Application, which can be used to produce images in SVG format with the jitter effect of the 2D Animation, was developed using Java language.